Perkin-Elmer gas chromatograph in use at Philadelphia police laboratory - Perkin-Elmer Corporation (1970)
Close-up view of a police officer transferring a vial of blood to a technician for blood alcohol analysis at a laboratory associated with the Philadelphia Police Department. Per notations accompanying the photograph, the Perkin-Elmer Model F-40 Automated Gas Chromatograph visible to the left of the technician is used as a forensic tool to measure the blood alcohol levels of drunk-driving suspects.
Keywords: Employees; Perkin-Elmer Corporation; Blood alcohol; Blood alcohol--Testing; Laboratories; Philadelphia (Pa.). Police Department; Corporations; Gas chromatography; Gas chromatography--Instruments; Scientific apparatus and instruments